Clinical efficacy of hysteroscopic adhesiolysis combined with periodic balloon dilation for intrauterine adhesion in IVF treatment - Chen, Yuanhui; Wang, Yiwen; Zhao, Yan; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
Background: Intrauterine adhesions (IUA), arising from diverse etiological factors, pose a significant threat to female fertility, particularly during in vitro fertilization (IVF) treatment. Objective: To assess the effectiveness of hysteroscopic adhesiolysis (HA) combined with periodic balloon dilation in treating IUA and its impact on reproductive outcomes in women undergoing IVF treatment. Methods: A total of 234 patients diagnosed with IUA were included in this study. The IUA women were categorized into three subgroups based on the severity of adhesion. All IUA patients underwent HA separation followed by periodic balloon dilation along with hormone replacement therapy (HRT). Frozen embryo transfer was performed post-treatment, and a comparative analysis of the general characteristics and clinical outcomes among the subgroups was conducted. The control group consisted of patients who underwent their first embryo transfer of HRT cycle without any uterine abnormalities, as assessed by the propensity score matching (PISM). The clinical outcomes of IUA group and control group were compared. Multivariate logistic regression analyses were employed to investigate the risk factors associated with live birth. Results: ① The endometrial thickness was significantly increased post-operation compared to pre-operation in all three IUA subgroups (all P <0.001), with the most pronounced change observed in the severe IUA group. After treatment, normal uterine cavity was restored in 218 women (93.16%). ② The overall clinical pregnancy rate was 49.57% (116/234) and live birth rate was 29.91% (70/234). The clinical outcomes were similar among the three subgroups after first embryo transfer (all P>0.05). Multivariate logistic regression analyses revealed that age (aOR 0.878, 95% CI 0.817~0.944, P=0.001) and endometrial thickness after treatment (aOR 1.292, 95% CI 1.046~1.597, P=0.018) were the two significant risk factors for live birth rate. ③ Following the process of matching, a total of 114 patients were successfully enrolled in the control group. The baselines and the clinical outcomes were all comparable between the IUA group and control group (all P>0.05). Conclusions: The combination of HA and periodic balloon dilation is beneficial for improving endometrial receptivity and has a significant clinical impact on patients with IUA undergoing IVF.